Incorporation of Functionalized Multiwall Carbon Nanotubes into a Polyurethane Matrix - Martin Michálek; Michael Bredol (Advances in Materials Science and Engineering)
Functionalized and raw multiwall carbon nanotubes (MWCNTs) were investigated colloid-chemically in order to study the role of polar versus nonpolar interaction with a polyurethane (PU) matrix. Both kinds of MWCNTs were dispersed by ultrasonication in the presence of a surfactant (sodium dodecyl sulphate) in aqueous solution. Functional groups on the nanotube surface were characterized by infrared spectroscopy and by the ζ-potential in aqueous suspension. Such suspensions were added to waterborne PU dispersions, drop-cast on glass substrates and cured. The percolation threshold for electrical conductivity with polar (functionalized) MWCNTs was reached at 0.24 wt.%, whereas at concentrations as high as 2 wt.%, PU films with nonpolar MWCNTs stayed below the percolation threshold. With an addition of 0.4 wt.% polar MWCNTs, the electrical conductivity increased to >10−6 S/cm in the cured coating layer. These results are interpreted with respect to the chemical nature of the PU matrix.